Influence of maternal and cord blood C‐reactive protein on childhood respiratory symptoms and eczema. Issue 5 (16th June 2013) - Sonnenschein‐van der Voort, Agnes M. M.; Jaddoe, Vincent W. V.; Moll, Henriëtte A.; Hofman, Albert; van der Valk, Ralf J. P.; de Jongste, Johan C.; Duijts, Liesbeth
Abstract: Background: Inflammatory processes during pregnancy might affect fetal lung development and immune responses. We examined the associations of maternal and cord blood C‐reactive protein levels with respiratory symptoms and eczema in preschool children. Methods: This study was embedded in a population‐based prospective cohort study of 4984 children. Generalized estimating equations were used to assess the effect of C‐reactive protein levels on respiratory symptoms or eczema. C‐reactive protein levels were measured during early pregnancy and at birth. Wheezing, lower respiratory tract infections, and eczema until the age of 4 yr were annually obtained by questionnaires. Results: Maternal C‐reactive protein was not associated with the risks of wheezing and lower respiratory tract infections. Compared to children with maternal C‐reactive protein in the lowest quarter, children in the highest quarter had increased risks of eczema OR 1.20 (1.03, 1.40). Compared to children with cord blood C‐reactive protein lower than 0.20 mg/l, those with levels higher than 0.20 mg/l had increased risks of wheezing, OR 1.21 (1.07, 1.36), and lower respiratory tract infections, OR 1.21 (1.05, 1.39), but not of eczema. Conclusions: Our results suggest that elevated maternal C‐reactive protein in pregnancy is associated with a higher risk of eczema, and C‐reactive protein in cord blood with a higher risk of wheezing and lower respiratory tract infections in the first 4 yrs.